Controlling-based organizational and economic mechanism of enterprise activity planning - Korbutiak, Alina (My University, 2024)
In this article, the authors prove how introducing a control system for enterprises will, firstly, increase the level of business controllability and reduce the time for making managerial decisions. Secondly, it will help to control the company's assets and manage costs more effectively. Thirdly, it will significantly increase the profitability of joint-stock companies and ensure risk control and risk mitigation to increase the investment attractiveness of the business. Due to the variety of external and internal factors influencing the organization, there cannot be a one-size-fits-all recommendation for establishing a controlling function within a company. Empirical research shows that the most important influencing factors in controlling an organization are the size of the company and the dynamics of changes in the external business environment. In small enterprises, the chief accountant typically performs the controlling function, whose responsibilities include analytical accounting and budgeting. In larger enterprises, specialized departments are created with various tasks related to coordinating management processes and control. The relationship between control functions and environmental dynamics is quite interesting. In companies operating in a stable environment, the controller is seen as a recorder. In a limited variability of the external environment, the controller performs the role of a navigator, providing the company's departments with the most rational planning and control tools. In a turbulent environment, the number of problems that need to be addressed increases significantly. In such a situation, the controller emerges as an innovator who directly participates in problem-solving. In essence, controlling does not necessarily require a separate controller position. Instead, it implies the presence of specific tasks that the company's executives or management can perform. Initially, it is necessary to determine whether the controlling functions can be distributed among existing departments or if creating an independent controlling department is better.
Keywords: controlling crisis management enterprise management innovation innovator creative innovations